Molding resin composition and electronic component device
By using a resin composition for forming a sulfur-containing atomic epoxy resin and a specific copolymer in the production of electronic parts devices, the problem of insufficient mold release properties in the prior art is solved, and higher production efficiency and continuous forming properties are achieved.
Patent Information
- Application Number
- CN202380037381.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-22
- Filing Date
- 2023-11-21
- Publication Date
- 2025-03-04
AI Technical Summary
The existing epoxy resin compositions are insufficient in the production of electronic parts devices, which affects production efficiency and continuous forming properties.
The molding resin composition consisting of sulfur-containing atomic epoxy resin, hardener, release agent, inorganic filler and specific copolymers (copolymers of α-olefins and maleic anhydride and derivatives), is uniformly dispersed by the hydrophobic and hydrophilic structural units of the specific copolymer to improve the release property.
The mold release property of the resin composition for forming is significantly improved, so that the production efficiency and continuous forming properties of the electronic part device are improved.
Smart Images

Figure BDA0005109104710000021 
Figure BDA0005109104710000022 
Figure BDA0005109104710000051
Abstract
Description
Technical Field
[0001] The present disclosure relates to a molding resin composition and an electronic component device. Background Art
[0002] In the field of component sealing of electronic parts such as transistors, integrated circuits (ICs), and large scale integrations (LSIs), resin sealing has become the mainstream in terms of productivity, cost, etc., and epoxy resin compositions are widely used as epoxy resin molding materials for sealing. The reason is that epoxy resins are excellent in the balance of various properties such as electrical properties, moisture resistance, heat resistance, mechanical properties, and adhesion to embedded products.
[0003] In order to improve the production efficiency and good continuous formability of electronic parts devices, a release agent is generally added to the epoxy resin composition for the purpose of smooth demolding from the mold. As a release agent, there are reports of copolymers of α-olefins and maleic anhydride (for example, refer to Patent Document 1), compounds obtained by esterifying copolymers of α-olefins and maleic anhydride (for example, refer to Patent Document 2 and Patent Document 3), oxidized polyolefins (for example, refer to Patent Document 4), etc. In addition, a method of achieving good demolding properties and good packaging appearance by combining a release agent as an oxidized polyolefin wax compound and a copolymer of α-olefins and maleic anhydride or maleic anhydride derivatives has also been reported (for example, refer to Patent Document 5).
[0004] Patent Document 1: Japanese Patent Laid-Open No. 10-36486
[0005] Patent Document 2: Japanese Patent Application Publication No. 2001-247748
[0006] Patent Document 3: Japanese Patent Application Publication No. 2003-64239
[0007] Patent Document 4: Japanese Patent Application Publication No. 2006-182913
[0008] Patent Document 5: Japanese Patent Application Publication No. 2005-255978 Summary of the invention
[0009] [Problems to be solved by the invention]
[0010] In order to improve the production efficiency of electronic component devices and achieve good continuous moldability, it is desired to further improve the mold release properties of epoxy resin compositions.
[0011] The present disclosure has been made in view of the above-mentioned conventional situation, and an object of the present invention is to provide a molding resin composition having excellent mold release properties, and an electronic component device using the same.
[0012] [Technical means to solve the problem]
[0013] The specific means for achieving the above-mentioned objects are as follows.
[0014] <1> A molding resin composition comprising: a sulfur atom-containing epoxy resin; a hardener; a release agent; an inorganic filler; and a copolymer of an α-olefin having 5 to 30 carbon atoms and at least one of maleic anhydride and a maleic anhydride derivative.
[0015] <2> The molding resin composition according to <1>, wherein the sulfur atom-containing epoxy resin contains a compound represented by the following general formula (B).
[0016] [Chemistry 1]
[0017]
[0018] (In the general formula (B), R 10 represents a hydrogen atom or a monovalent organic group having 1 to 18 carbon atoms, which may be all the same or different; n is an average value and represents a number from 0 to 10)
[0019] <3> The molding resin composition according to <1> or <2>, wherein the release agent comprises oxidized polyethylene.
[0020] <4> The molding resin composition according to <3>, wherein the oxidized polyethylene includes a linear oxidized polyethylene.
[0021] <5> The molding resin composition according to <3> or <4>, wherein the oxidized polyethylene includes a branched oxidized polyethylene.
[0022] <6> The molding resin composition according to any one of <3> to <5>, wherein the weight average molecular weight of the oxidized polyethylene is 2,800 or more.
[0023] <7> The molding resin composition according to any one of <3> to <6>, wherein the acid value of the oxidized polyethylene is 2 mgKOH / g to 50 mgKOH / g.
[0024] <8> The molding resin composition according to any one of <1> to <7>, wherein the copolymer includes a structural unit represented by the following general formula (C) and a structural unit represented by the following general formula (D).
[0025] [Chemistry 2]
[0026]
[0027] (In general formula (C) and general formula (D), R 11 represents a monovalent aliphatic hydrocarbon group having 3 to 28 carbon atoms, R 12 and R 13 each independently represents a hydrogen atom, an alkyl group or an aryl group)
[0028] <9> An electronic component device comprising: a support member; an electronic component disposed on the support member; and a cured product of the molding resin composition according to any one of <1> to <8> that seals the electronic component.
[0029] [Effects of the Invention]
[0030] According to the present disclosure, a molding resin composition having excellent mold releasability and an electronic component device using the same can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a graph showing changes in shear demolding strength of Examples 1 to 5 and Comparative Examples 1 to 3.
[0032] Figure 2 It is a graph showing changes in shear demolding strength regarding Example 6 and Comparative Example 4. DETAILED DESCRIPTION
[0033] Hereinafter, the embodiments of the present disclosure are described in detail. However, the present disclosure is not limited to the following embodiments. In the following embodiments, the components (including component steps, etc.) are not required except for the cases specifically indicated. The same is true for the numerical values and their ranges, which do not limit the present disclosure.
[0034] In the present disclosure, the term "process" includes processes that are independent of other processes and processes that cannot be clearly distinguished from other processes as long as the purpose of the process is achieved.
[0035] In the present disclosure, in a numerical range represented by “to”, numerical values described before and after including “to” are respectively regarded as the minimum value and the maximum value.
[0036] In the numerical range recorded in stages in the present disclosure, the upper limit or lower limit recorded in one numerical range may also be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in the present disclosure, the upper limit or lower limit of the numerical range may also be replaced by the value shown in the embodiment.
[0037] In the present disclosure, each component may include multiple equivalent substances. When multiple substances equivalent to each component exist in the composition, unless otherwise specified, the content or content of each component refers to the total content or content of the multiple substances present in the composition.
[0038] In the present disclosure, particles corresponding to each component may include multiple types of particles. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component refers to the value of the mixture of the multiple types of particles present in the composition unless otherwise specified.
[0039] <Molding resin composition>
[0040] The molding resin composition disclosed herein contains: a sulfur-containing epoxy resin; a hardener; a release agent; an inorganic filler; and a copolymer of an α-olefin having 5 to 30 carbon atoms and at least one of maleic anhydride and a maleic anhydride derivative (hereinafter sometimes referred to as a specific copolymer).
[0041] The molding resin composition disclosed in the present invention has excellent mold releasability. The reason for this is not clear, but is presumed as follows.
[0042] The specific copolymer has a hydrophobic structural unit derived from an α-olefin having 5 to 30 carbon atoms and a hydrophilic structural unit derived from at least one of maleic anhydride and a maleic anhydride derivative in the molecule. Therefore, by using the specific copolymer, the mold release agent can be well dispersed in the epoxy resin, and when the molding resin composition is cured to obtain a cured product, the mold release agent can be easily and uniformly dispersed in the cured product.
[0043] In addition, by using a sulfur-containing epoxy resin, the mold release agent easily seeps out to the surface of the cured product.
[0044] The mold release agent uniformly dispersed in the cured product easily seeps out from the surface of the cured product evenly. Therefore, the cured product easily comes off from the mold. Furthermore, by repeatedly sealing the electronic component in a state where the mold release agent seeping out from the surface of the cured product adheres to the surface of the mold, the amount of the mold release agent adhered to the surface of the mold increases, so that the cured product easily comes off from the mold.
[0045] From the above, it is estimated that the molding resin composition of the present disclosure is excellent in mold releasability.
[0046] Hereinafter, each component constituting the molding resin composition will be described. The molding resin composition of the present disclosure contains a sulfur atom-containing epoxy resin as an epoxy resin, a hardener, a release agent, an inorganic filler, and a specific copolymer, and may contain other components as necessary.
[0047] (Epoxy resin)
[0048] The molding resin composition of the present disclosure contains a sulfur-containing epoxy resin as the epoxy resin. The molding resin composition of the present disclosure may contain other epoxy resins other than the sulfur-containing epoxy resin.
[0049] When the molding resin composition of the present disclosure contains other epoxy resins, the proportion of the sulfur atom-containing epoxy resin in the epoxy resin is preferably 5 to 50% by mass, more preferably 10 to 40% by mass, and even more preferably 18 to 30% by mass.
[0050] From the viewpoints of strength, fluidity, heat resistance, moldability, etc., the mass ratio of the epoxy resin in the entire molding resin composition is preferably 0.5 mass % to 30 mass %, more preferably 2 mass % to 20 mass %, and further preferably 3.5 mass % to 13 mass %.
[0051] The structure of the sulfur-containing epoxy resin is not particularly limited as long as it contains a sulfur atom in the molecule. The sulfur-containing epoxy resin may contain, for example, an epoxy compound having a diphenyl sulfide structure, or a compound represented by the following general formula (B).
[0052] [Chemistry 3]
[0053]
[0054] In the general formula (B), R 10 represents a hydrogen atom or a monovalent organic group having 1 to 18 carbon atoms, and all of them may be the same or different. n is an average value and represents a number of 0 to 10.
[0055] As R 10 Examples of the monovalent organic group having 1 to 18 carbon atoms include alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, pentyl, hexyl, cyclopentyl and cyclohexyl, aryl groups such as phenyl and tolyl, and alkoxy groups such as methoxy, ethoxy, propoxy and butoxy.
[0056] In the compound represented by the general formula (B), R 10 The positions of the oxygen atoms in the molecule are 4-position and 4'-position, 3-position and 3'-position are tert-butyl, 6-position and 6'-position are methyl, and the other R 10 YSLV-120TE (trade name of NIPPON STEEL Chemical & Material Co., Ltd.) or the like which is a hydrogen atom is available as a commercial product.
[0057] The type of other epoxy resins is not particularly limited as long as they have an epoxy group in the molecule.
[0058] Other epoxy resins include, specifically, novolac-type epoxy resins (phenol novolac-type epoxy resins, o-cresol novolac-type epoxy resins, etc.) obtained by condensing or co-condensing at least one phenolic compound selected from the group consisting of phenolic compounds such as phenol, cresol, xylenol, resorcinol, catechol, bisphenol A, bisphenol F, and naphthol compounds such as α-naphthol, β-naphthol, and dihydroxynaphthalene with an aliphatic aldehyde compound such as formaldehyde, acetaldehyde, and propionaldehyde under an acidic catalyst to obtain a novolac resin, and then epoxidizing the novolac resin; and novolac-type epoxy resins (phenol novolac-type epoxy resins, o-cresol novolac-type epoxy resins, etc.) obtained by condensing or co-condensing the phenolic compound with an aromatic aldehyde compound such as benzaldehyde and salicylaldehyde under an acidic catalyst to obtain a triphenylmethane-type phenol resin, and then epoxidizing the triphenylmethane-type phenol resin. triphenylmethane epoxy resin obtained by epoxidation; copolymerized epoxy resin obtained by epoxidizing a novolac resin obtained by co-condensing the phenol compound and naphthol compound with an aldehyde compound under an acidic catalyst; diphenylmethane epoxy resin as a diglycidyl ether of bisphenol A, bisphenol F, etc.; biphenyl epoxy resin as a diglycidyl ether of an alkyl-substituted or unsubstituted biphenol; distyrene epoxy resin as a diglycidyl ether of a distyrene phenol compound; epoxy resin as a glycidyl ether of alcohols such as butanediol, polyethylene glycol, and polypropylene glycol; glycidyl ester epoxy resin as a glycidyl ester of a polycarboxylic acid compound such as phthalic acid, isophthalic acid, and tetrahydrophthalic acid; Glycidylamine epoxy resins obtained by replacing the active hydrogen bonded to the nitrogen atom of aniline, diaminodiphenylmethane, isocyanuric acid, etc. with a glycidyl group; dicyclopentadiene epoxy resins obtained by epoxidizing a co-condensation resin of dicyclopentadiene and a phenol compound; alicyclic epoxy resins such as diepoxy vinylcyclohexene, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, and 2-(3,4-epoxy)cyclohexyl-5,5-spiro(3,4-epoxy)cyclohexane-m-dioxane obtained by epoxidizing an olefin bond in the molecule; p-xylene-modified epoxy resins as glycidyl ethers of p-xylene-modified phenol resins; m-xylene-modified epoxy resins as glycidyl ethers of m-xylene-modified phenol resins; terpene Terpene-modified epoxy resins of glycidyl ethers of olefin-modified phenol resins; dicyclopentadiene-modified epoxy resins as glycidyl ethers of dicyclopentadiene-modified phenol resins; cyclopentadiene-modified epoxy resins as glycidyl ethers of cyclopentadiene-modified phenol resins; polycyclic aromatic ring-modified epoxy resins as glycidyl ethers of polycyclic aromatic ring-modified phenol resins; naphthalene-type epoxy resins as glycidyl ethers of phenol resins containing naphthalene rings; halogenated phenol novolac-type epoxy resins; hydroquinone-type epoxy resins; trimethylolpropane-type epoxy resins; linear aliphatic epoxy resins obtained by oxidizing olefin bonds using peracids such as peracetic acid; aralkyl-type epoxy resins obtained by epoxidizing aralkyl-type phenol resins such as phenol aralkyl resins, naphthol aralkyl resins, and biphenyl aralkyl resins, etc.Furthermore, epoxides of acrylic resins and the like can also be mentioned as epoxy resins. Other epoxy resins may be used alone or in combination of two or more.
[0059] The other epoxy resin preferably includes at least any one of a diphenylmethane epoxy resin, a triphenylmethane epoxy resin, an o-cresol novolac epoxy resin, and a biphenyl aralkyl epoxy resin, and more preferably includes a diphenylmethane epoxy resin or a biphenyl aralkyl epoxy resin.
[0060] The epoxy equivalent (molecular weight / number of epoxy groups) of the epoxy resin is not particularly limited. From the viewpoint of balancing various properties such as moldability, reflow resistance, and electrical reliability, the epoxy equivalent of the epoxy resin is preferably 100 g / eq to 1000 g / eq, and more preferably 150 g / eq to 500 g / eq.
[0061] The epoxy equivalent of the epoxy resin is defined as a value measured by a method in accordance with Japanese Industrial Standards (JIS) K 7236:2009.
[0062] When the epoxy resin is solid, the softening point or melting point of the epoxy resin is not particularly limited. From the viewpoint of moldability and reflow resistance, the softening point or melting point of the epoxy resin is preferably 40°C to 180°C, and from the viewpoint of operability during preparation of the molding resin composition, it is more preferably 50°C to 130°C.
[0063] The melting point or softening point of the epoxy resin is defined as a value measured by differential scanning calorimetry (DSC) or a method (ring and ball method) in accordance with JIS K 7234: 1986.
[0064] (Hardener)
[0065] The molding resin composition of the present disclosure contains a curing agent.
[0066] As a hardener, from the viewpoint of formability and reliability, a phenol hardener is preferably used. As a hardener, from the viewpoint of suppressing the dielectric constant and dielectric loss tangent of the hardened material to be low, an active ester compound is preferably used. As a hardener, other hardeners other than a phenol hardener and an active ester compound may also be used. As other hardeners, anhydride hardeners, amine hardeners, etc. may be cited.
[0067] The molding resin composition may contain only one type of curing agent, or may contain two or more types of curing agents.
[0068] When the molding resin composition contains two or more curing agents, two or more phenol curing agents may be used, two or more active ester compounds may be used, or a phenol curing agent and an active ester compound may be used in combination.
[0069] -Active ester compound-
[0070] Here, the active ester compound refers to a compound having one or more ester groups reactive with an epoxy group in one molecule and having a curing effect on the epoxy resin.
[0071] When an active ester compound is used as a curing agent, the dielectric constant and dielectric loss tangent of the cured product can be suppressed to be lower than when a phenol curing agent is used alone as a curing agent. The reason for this is presumably as follows.
[0072] In the reaction between epoxy resin and phenol hardener, secondary hydroxyl groups are generated. In contrast, in the reaction between epoxy resin and active ester compound, ester groups are generated instead of secondary hydroxyl groups. It is speculated that since ester groups have lower polarity than secondary hydroxyl groups, the molding resin composition containing active ester compounds as hardeners can suppress the dielectric constant and dielectric loss tangent of the hardened material to be lower than the molding resin composition containing only a hardener that generates secondary hydroxyl groups as a hardener.
[0073] In addition, the polar groups in the cured product increase the water absorption of the cured product. By using an active ester compound as a curing agent, the concentration of polar groups in the cured product can be suppressed, and the water absorption of the cured product can be suppressed. In addition, it is speculated that by suppressing the water absorption of the cured product, that is, suppressing the content of H2O as a polar molecule, the dielectric constant and dielectric loss tangent of the cured product can be suppressed to a lower level.
[0074] The type of active ester compound is not particularly limited as long as it has one or more ester groups reactive with epoxy groups in the molecule. Examples of active ester compounds include phenol ester compounds, thiophenol ester compounds, N-hydroxylamine ester compounds, and esters of heterocyclic hydroxyl compounds.
[0075] Examples of the active ester compound include ester compounds obtained from at least one of an aliphatic carboxylic acid and an aromatic carboxylic acid and at least one of an aliphatic hydroxyl compound and an aromatic hydroxyl compound. An ester compound using an aliphatic compound as a polycondensation component tends to have excellent compatibility with epoxy resins due to the presence of an aliphatic chain. An ester compound using an aromatic compound as a polycondensation component tends to have excellent heat resistance due to the presence of an aromatic ring.
[0076] As specific examples of active ester compounds, aromatic esters obtained by condensation reaction of aromatic carboxylic acids and phenolic hydroxyl groups can be cited. Among them, aromatic carboxylic acid components obtained by replacing 2 to 4 hydrogen atoms of aromatic rings such as benzene, naphthalene, biphenyl, diphenylpropane, diphenylmethane, diphenyl ether, diphenylsulfonic acid with carboxyl groups, monohydric phenols obtained by replacing 1 hydrogen atom of the aromatic ring with hydroxyl groups, and mixtures of polyhydric phenols obtained by replacing 2 to 4 hydrogen atoms of the aromatic ring with hydroxyl groups as raw materials are preferably used. Aromatic esters obtained by condensation reaction of aromatic carboxylic acids and phenolic hydroxyl groups. That is, aromatic esters having structural units derived from the aromatic carboxylic acid components, structural units derived from the monohydric phenols, and structural units derived from the polyhydric phenols are preferably used.
[0077] Specific examples of active ester compounds include phenol resins having a molecular structure in which a phenol compound is linked via an aliphatic cyclic hydrocarbon group, as described in Japanese Patent Laid-Open No. 2012-246367, and active ester resins having a structure obtained by reacting an aromatic dicarboxylic acid or a halide thereof with an aromatic monohydroxy compound. The active ester resin is preferably a compound represented by the following structural formula (1).
[0078] [Chemistry 4]
[0079]
[0080] In the structural formula (1), R 1 is a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a phenyl group; X is an unsubstituted benzene ring, an unsubstituted naphthalene ring, a benzene ring or a naphthalene ring substituted with an alkyl group having 1 to 4 carbon atoms, or a biphenyl group; Y is a benzene ring, a naphthalene ring, or a benzene ring or a naphthalene ring substituted with an alkyl group having 1 to 4 carbon atoms; k is 0 or 1; and n represents the average number of repetitions and is 0 to 5.
[0081] Specific examples of the compound represented by the structural formula (1) include the following exemplary compounds (1-1) to (1-10): t-Bu in the structural formula is a tert-butyl group.
[0082] [Chemistry 5]
[0083]
[0084] [Chemistry 6]
[0085]
[0086] Other specific examples of the active ester compound include a compound represented by the following structural formula (2) and a compound represented by the following structural formula (3) described in JP-A-2014-114352.
[0087] [Chemistry 7]
[0088]
[0089] In the structural formula (2), R 1 and R 2 are each independently a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms, Z is an ester-forming structural site (z1) or a hydrogen atom (z2) selected from the group consisting of an unsubstituted benzoyl group, an unsubstituted naphthoyl group, a benzoyl group or naphthoyl group substituted with an alkyl group having 1 to 4 carbon atoms, and an acyl group having 2 to 6 carbon atoms, and at least one of Z is an ester-forming structural site (z1).
[0090] In the structural formula (3), R 1 and R 2 are each independently a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms, Z is an ester-forming structural site (z1) or a hydrogen atom (z2) selected from the group consisting of an unsubstituted benzoyl group, an unsubstituted naphthoyl group, a benzoyl group or naphthoyl group substituted with an alkyl group having 1 to 4 carbon atoms, and an acyl group having 2 to 6 carbon atoms, and at least one of Z is an ester-forming structural site (z1).
[0091] Specific examples of the compound represented by the structural formula (2) include the following exemplary compounds (2-1) to (2-6).
[0092] [Chemistry 8]
[0093]
[0094] Specific examples of the compound represented by the structural formula (3) include the following exemplary compounds (3-1) to (3-6).
[0095] [Chemistry 9]
[0096]
[0097] As the active ester compound, commercially available products can also be used. As commercially available products of the active ester compound, the active ester compound containing a dicyclopentadiene type diphenol structure can be listed as "EXB9451", "EXB9460", "EXB9460S", "HPC-8000-65T" (manufactured by DIC Corporation); the active ester compound containing an aromatic structure can be listed as "EXB9416-70BK", "EXB-8", "EXB-9425" (manufactured by DIC Corporation); the active ester compound containing an acetylated product of phenol novolac can be listed as "DC808" (manufactured by Mitsubishi Chemical Corporation); the active ester compound containing a benzoylated product of phenol novolac can be listed as "YLH1026" (manufactured by Mitsubishi Chemical Corporation), etc.
[0098] The ester equivalent (molecular weight / number of ester groups) of the active ester compound is not particularly limited, but is preferably 150 g / eq to 400 g / eq, more preferably 170 g / eq to 300 g / eq, and even more preferably 200 g / eq to 250 g / eq from the viewpoint of balancing various properties such as formability, reflow resistance, and electrical reliability.
[0099] The ester equivalent of the active ester compound is set to a value measured by a method in accordance with JIS K 0070:1992.
[0100] -Phenol Hardener-
[0101] Specific examples of the phenol curing agent include: polyphenol compounds such as resorcinol, catechol, bisphenol A, bisphenol F, and substituted or unsubstituted biphenols; novolac-type phenol resins obtained by condensing or co-condensing at least one phenolic compound selected from the group consisting of phenol compounds such as phenol, cresol, xylenol, resorcinol, catechol, bisphenol A, bisphenol F, phenylphenol, aminophenol, and naphthol compounds such as α-naphthol, β-naphthol, and dihydroxynaphthalene with an aldehyde compound such as formaldehyde, acetaldehyde, and propionaldehyde in the presence of an acid catalyst; and polyphenol compounds such as polyphenols obtained by condensing or co-condensing the phenolic compounds with dimethoxy-p-xylene, bis(methoxymethyl)biphenyl, and the like. Synthetic aralkyl phenol resins such as phenol aralkyl resins and naphthol aralkyl resins; p-xylene-modified phenol resins and m-xylene-modified phenol resins; melamine-modified phenol resins; terpene-modified phenol resins; dicyclopentadiene-type phenol resins and dicyclopentadiene-type naphthol resins synthesized by copolymerizing the above-mentioned phenolic compounds with dicyclopentadiene; cyclopentadiene-modified phenol resins; polycyclic aromatic ring-modified phenol resins; biphenyl-type phenol resins; triphenylmethane-type phenol resins obtained by condensing or co-condensing the above-mentioned phenolic compounds with aromatic aldehyde compounds such as benzaldehyde and salicylaldehyde under an acidic catalyst; phenol resins obtained by copolymerizing two or more of these, etc. These phenolic hardeners may be used alone or in combination of two or more.
[0102] The hydroxyl equivalent of the phenol curing agent is not particularly limited, but is preferably 70 to 1000 g / eq, more preferably 80 to 500 g / eq, from the viewpoint of balancing various properties such as formability, reflow resistance, and electrical reliability.
[0103] The hydroxyl equivalent of the phenol curing agent is a value measured by a method in accordance with JIS K 0070:1992.
[0104] The equivalent ratio of epoxy resin to hardener, i.e., the ratio of the number of functional groups in the hardener to the number of functional groups in the epoxy resin (number of functional groups in the hardener / number of functional groups in the epoxy resin) is not particularly limited. From the viewpoint of suppressing the respective unreacted components to a small extent, it is preferably set in the range of 0.5 to 2.0, and more preferably in the range of 0.6 to 1.3. From the viewpoint of formability and reflow resistance, it is further preferably set in the range of 0.8 to 1.2.
[0105] When an active ester compound and a phenol curing agent are used in combination as the curing agent, the molar ratio of the ester group contained in the active ester compound to the phenolic hydroxyl group contained in the phenol curing agent (ester group / phenolic hydroxyl group) is preferably 9 / 1 to 1 / 9, more preferably 8 / 2 to 2 / 8, and further preferably 3 / 7 to 7 / 3.
[0106] When an active ester compound and a phenol curing agent are used together as a curing agent, the mass ratio of the active ester compound in the total amount of the active ester compound and the phenol curing agent is preferably 40 mass % to 90 mass %, more preferably 50 mass % to 80 mass %, and further preferably 55 mass % to 70 mass %, from the viewpoint of achieving excellent flexural strength of the molding resin composition after curing and suppressing the dielectric loss tangent of the cured product to be low.
[0107] When an active ester compound and a phenol curing agent are used together as a curing agent, the mass ratio of the phenol curing agent in the total amount of the active ester compound and the phenol curing agent is preferably 10 mass % to 60 mass %, more preferably 20 mass % to 50 mass %, and further preferably 30 mass % to 45 mass %, from the viewpoint of achieving excellent flexural strength of the molding resin composition after curing and suppressing the dielectric loss tangent of the cured product to be low.
[0108] The softening point or melting point of the curing agent is not particularly limited. From the viewpoint of moldability and reflow resistance, the softening point or melting point of the curing agent is preferably 40°C to 180°C, and from the viewpoint of workability during production of the molding resin composition, more preferably 50°C to 130°C.
[0109] The melting point or softening point of the curing agent is set to a value measured in the same manner as the melting point or softening point of the epoxy resin.
[0110] (Inorganic filler)
[0111] The molding resin composition disclosed in the present invention contains an inorganic filler. The type of inorganic filler is not particularly limited. Specifically, inorganic materials such as silica such as fused silica and crystalline silica, glass, alumina, aluminum nitride, boron nitride, talc, clay, mica, calcium titanate, and barium titanate can be listed. Inorganic fillers with flame retardant effects can also be used. Examples of inorganic fillers with flame retardant effects include composite metal hydroxides such as aluminum hydroxide, magnesium hydroxide, composite hydroxides of magnesium and zinc, and zinc borate.
[0112] In inorganic filler, with respect to the viewpoint of reducing the linear expansion coefficient, preferably silicon dioxide such as fused silica, with respect to the viewpoint of high thermal conductivity, preferably aluminum oxide. With respect to the viewpoint of further reducing the dielectric loss tangent, preferably boron nitride. Inorganic filler can be used alone or in combination of two or more. As the form of inorganic filler, powder, beads, fibers, etc., which are sphericalized powders, can be listed.
[0113] The average particle size of the inorganic filler is not particularly limited. For example, the volume average particle size is preferably 0.2 μm to 50 μm, and more preferably 0.5 μm to 30 μm.
[0114] If the volume average particle size is more than 0.2 μm, there is a tendency that the viscosity of the molding resin composition is further suppressed. If the volume average particle size is less than 50 μm, there is a tendency that the filling property of the narrow gap is further improved. The volume average particle size of the inorganic filler refers to the value obtained by measuring the particle size distribution of the laser diffraction scattering method as the volume average particle size (D50).
[0115] The volume average particle size of the inorganic filler in the molding resin composition or its cured product can be measured by a known method. As an example, an organic solvent, nitric acid, aqua regia, etc. are used to extract the inorganic filler from the molding resin composition or the cured product, and the dispersion is fully dispersed using an ultrasonic disperser, etc., to prepare a dispersion. The volume average particle size of the inorganic filler can be measured according to the particle size distribution of the volume basis obtained by using the dispersion and measuring the obtained by a laser diffraction scattering method particle size distribution measuring device. Alternatively, the volume average particle size of the inorganic filler can be measured according to the particle size distribution of the volume basis obtained by observing the cross section obtained by burying the cured product in a transparent epoxy resin, etc. and grinding it using a scanning electron microscope. Furthermore, it is also possible to continuously observe the two-dimensional cross section of the cured product using a focused ion beam (Focused Ion Beam, FIB) device (focused ion beam scanning electron microscope (Scanning Electron Microscope, SEM)) and the like and perform three-dimensional structural analysis and measure.
[0116] From the viewpoint of the fluidity of the molding resin composition, the particle shape of the inorganic filler is preferably spherical rather than square, and the particle size distribution of the inorganic filler is preferably distributed over a wide range.
[0117] From the viewpoint of controlling the fluidity and strength of the cured product of the molding resin composition, the content of the inorganic filler as a whole contained in the molding resin composition is preferably greater than 50% by volume, more preferably greater than 55% by volume, further preferably greater than 55% by volume and less than 90% by volume, and particularly preferably 60% to 85% by volume, relative to the molding resin composition as a whole.
[0118] The content (volume %) of the inorganic filler in the molding resin composition can be determined by the following method.
[0119] A thin slice sample of a cured product of the molding resin composition is photographed using a scanning electron microscope (SEM). An arbitrary area S is determined in the SEM image, and the total area A of the inorganic filler contained in the area S is obtained. The value obtained by dividing the total area A of the inorganic filler by the area S is converted into a percentage (%), and the value is set as the content (volume %) of the inorganic filler in the molding resin composition.
[0120] The area S is set to be sufficiently large relative to the size of the inorganic filler. For example, it is set to be large enough to contain 100 or more inorganic fillers. The area S may also be the total of a plurality of cut surfaces.
[0121] Inorganic fillers may have a ratio deviation in the gravity direction when the molding resin composition is cured. In such a case, when photographing with SEM, the entire hardened material in the gravity direction is photographed, and the area S including the entire hardened material in the gravity direction is determined.
[0122] (Release Agent)
[0123] From the viewpoint of obtaining good demolding properties from the mold during molding, the molding resin composition disclosed herein includes a mold release agent. The mold release agent is not particularly limited, and a known mold release agent can be used. Specifically, examples include: palm wax, montanic acid, stearic acid and other higher fatty acids, higher fatty acid metal salts, ester waxes such as montanic acid esters, oxidized polyethylene, non-oxidized polyethylene and other polyolefin waxes, etc. The mold release agent can be used alone or in combination of two or more.
[0124] From the viewpoint of mold release, fluidity and package contamination, the mold release agent preferably contains a polyolefin wax, and more preferably contains oxidized polyethylene. The oxidized polyethylene may be a linear oxidized polyethylene or a branched oxidized polyethylene. A linear oxidized polyethylene and a branched oxidized polyethylene may also be used in combination.
[0125] Here, the so-called linear polyethylene oxide refers to polyethylene oxide in which the carbon number of the side chain alkyl chain is less than about 10% of the carbon number of the main chain alkyl chain. Generally speaking, polyethylene oxide with a needle penetration of less than 2 is classified as linear polyethylene oxide. Compared with branched polyethylene oxide of the same molecular weight and acid value, linear polyethylene oxide tends to have high alkyl chain efficiency, easy to ooze out from the base resin, and high mold release properties. The greater the amount of inorganic filler, and the larger the weight average molecular weight of the linear polyethylene oxide, the more obvious the tendency.
[0126] From the viewpoint of mold release, the weight average molecular weight of the oxidized polyethylene is preferably 2800 or more, and from the viewpoint of adhesion and prevention of mold-package contamination, the weight average molecular weight of the oxidized polyethylene is preferably 30000 or less, more preferably 2800 to 30000, further preferably 2900 to 20000, and particularly preferably 3000 to 15000. Here, the weight average molecular weight refers to the value measured by high temperature gel permeation chromatography (GPC). The measuring method is as follows.
[0127] Measuring instrument: High temperature GPC manufactured by Waters
[0128] Column: PLgel 10 μm MIXED-B (7.5 mm × 300 mm) × 2 manufactured by Polymer Laboratories
[0129] Flow rate: 1.0 ml / min (sample concentration: 0.3 w / vol%)
[0130] Injection volume: 100 μl
[0131] In terms of the balance between package contamination and mold release properties, the acid value of the oxidized polyolefin is preferably 2 mgKOH / g to 50 mgKOH / g, more preferably 10 mgKOH / g to 40 mgKOH / g, and still more preferably 15 mgKOH / g to 30 mgKOH / g. When the acid value is 5 mgKOH / g or more, package contamination tends to be more easily suppressed, and when it is 50 mgKOH / g or less, mold release properties tend to be further improved.
[0132] In the present disclosure, the acid value of the oxidized polyolefin is defined as a value measured by a method in accordance with JIS K 5902:1969.
[0133] The content of the release agent is preferably 1 to 30 parts by mass, more preferably 5 to 25 parts by mass, and further preferably 7 to 20 parts by mass, relative to 100 parts by mass of the sulfur-containing epoxy resin. If the amount of the release agent is 1 part by mass or more relative to 100 parts by mass of the sulfur-containing epoxy resin, there is a tendency that sufficient releasability can be obtained. If it is 30 parts by mass or less, there is a tendency that better adhesion can be obtained.
[0134] The content of the release agent is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the total of the epoxy resin and the hardener. If the amount of the release agent is 0.01 parts by mass or more relative to 100 parts by mass of the total of the epoxy resin and the hardener, there is a tendency that sufficient releasability can be obtained. If it is 10 parts by mass or less, there is a tendency that better adhesion can be obtained.
[0135] When the release agent contains polyethylene oxide, the content of polyethylene oxide is preferably 1 to 30 parts by mass, more preferably 5 to 25 parts by mass, and further preferably 7 to 20 parts by mass relative to 100 parts by mass of the sulfur-containing epoxy resin. If the amount of polyethylene oxide is 1 part by mass or more relative to 100 parts by mass of the sulfur-containing epoxy resin, there is a tendency that sufficient release properties can be obtained. If it is 30 parts by mass or less, there is a tendency that better adhesion can be obtained.
[0136] The content of the oxidized polyethylene is preferably 0.01 to 10 parts by mass, and more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the total of the epoxy resin and the hardener. If the amount of the oxidized polyethylene is 0.01 parts by mass or more relative to 100 parts by mass of the total of the epoxy resin and the hardener, there is a tendency that sufficient mold release properties can be obtained. If it is 10 parts by mass or less, there is a tendency that better adhesion can be obtained.
[0137] (Specific copolymer)
[0138] The molding resin composition of the present disclosure contains a specific copolymer.
[0139] The α-olefin having 5 to 30 carbon atoms used in the specific copolymer is not particularly limited. Specific examples of the α-olefins having 5 to 30 carbon atoms include linear α-olefins such as 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene ... Among them, linear α-olefins having 10 to 25 carbon atoms are preferred, and linear α-olefins having 15 to 25 carbon atoms, such as 1-eicosene, 1-docosene, and 1-tricosene, are more preferred.
[0140] Examples of the maleic anhydride derivative used in the specific copolymer include methyl maleic anhydride and dimethyl maleic anhydride.
[0141] The specific copolymer preferably includes a structural unit represented by the following general formula (C) and a structural unit represented by the following general formula (D).
[0142] [Chemistry 10]
[0143]
[0144] In the general formula (C) and the general formula (D), R 11 represents a monovalent aliphatic hydrocarbon group having 3 to 28 carbon atoms, R 12 and R 13 Each independently represents a hydrogen atom, an alkyl group or an aryl group.
[0145] In the general formula (C), R 11Specific examples of the monovalent aliphatic hydrocarbon group having 3 to 28 carbon atoms represented by include a monovalent residue obtained by removing a vinyl group (-CH=CH2) from the above-mentioned α-olefin having 5 to 30 carbon atoms. 11 , preferably a straight-chain hydrocarbon group having 13 to 23 carbon atoms, more preferably a straight-chain hydrocarbon group having 18 to 21 carbon atoms such as n-octadecyl, n-eicosyl, and n-heneicosyl.
[0146] In the general formula (D), R 12 or R 13 The alkyl group shown in the figure includes an alkyl group having 1 to 4 carbon atoms, and a methyl group is preferred.
[0147] In the general formula (D), R 12 or R 13 The aryl group shown is preferably phenyl.
[0148] In the general formula (D), R 12 or R 13 Preferred is a hydrogen atom.
[0149] The copolymerization ratio of the structural unit represented by the general formula (C) and the structural unit represented by the general formula (D) is not particularly limited. When the structural unit represented by the general formula (C) is set to X moles and the structural unit represented by the general formula (D) is set to Y moles, X / Y is preferably 1 / 2 to 10 / 1, more preferably 2 / 3 to 5 / 1, further preferably 3 / 4 to 2 / 1, and particularly preferably about 1 / 1, which is approximately equimolar.
[0150] When the structural unit represented by the general formula (C) is bonded to the structural unit represented by the general formula (D), it may be in any state of the following general formula (E) and the following general formula (F). 11 ~R 13 Specific examples and preferred examples are the same as those of the general formula (C) and the general formula (D).
[0151] [Chemistry 11]
[0152]
[0153] The specific copolymer may have any structure such as a random, block, or graft copolymer.
[0154] When the specific copolymer includes the structural unit represented by the general formula (C) and the structural unit represented by the general formula (D), other structural units other than the structural unit represented by the general formula (C) and the structural unit represented by the general formula (D) may be included or not. The proportion of other structural units in all structural units of the specific copolymer is preferably 0 mol% to 50 mol%, more preferably 0 mol% to 35 mol%, and further preferably 0 mol% to 20 mol%.
[0155] Regarding the specific copolymer, at least a part of the structural unit derived from at least one of maleic anhydride and a maleic anhydride derivative contained in the specific copolymer can be hydrolyzed to have a carboxyl group.
[0156] There is no particular limitation on the method for producing a specific copolymer, and a general copolymerization method such as reacting raw materials can be used. An organic solvent that can dissolve α-olefins and maleic anhydride can also be used in the reaction. As an organic solvent, there is no particular limitation, and toluene is preferred. Alcoholic solvents, etheric solvents, amine solvents, etc. can also be used. The reaction temperature varies depending on the type of organic solvent used. From the perspective of reactivity and productivity, it is preferably set to 50°C to 200°C, and more preferably 80°C to 120°C. As long as a specific copolymer can be obtained, the reaction time is not particularly limited. From the perspective of productivity, it is preferably set to 1 hour to 30 hours, more preferably 2 hours to 15 hours, and further preferably 4 hours to 10 hours. After the reaction is completed, unreacted components, organic solvents, etc. can be removed under heating and reduced pressure as needed. The conditions are preferably set to a temperature of 100°C to 220°C, more preferably 120°C to 180°C and a pressure of 13.3×10 3 Pa or less, more preferably 8×10 3 Pa or less, and the reaction time is 0.5 to 10 hours. In addition, a reaction catalyst such as an amine catalyst or an acid catalyst may be added during the reaction as needed. The pH value of the reaction system is preferably about 1 to 10.
[0157] A commercial product may be used as the specific copolymer. As a commercial product, NISSAN ELECTOL WPB-1 (trade name manufactured by NOF Corporation) using 1-eicosene, 1-docosene, and 1-tricosene as raw materials is available.
[0158] From the viewpoint of preventing mold-package contamination and moldability, the weight average molecular weight of the specific copolymer is preferably 5000 to 100000, more preferably 10000 to 70000, and further preferably 15000 to 50000. When the weight average molecular weight is 5000 or more, the mold-package contamination prevention effect tends to be sufficient, and when it is 100000 or less, the softening point of the specific copolymer does not rise excessively and the deterioration of the kneading property and the like tends to be suppressed.
[0159] Here, the weight average molecular weight of the specific copolymer is derived by measuring it by gel permeation chromatography (GPC) and converting it using a calibration curve of standard polystyrene. The conditions of GPC are as follows.
[0160] -GPC conditions-
[0161] Pump: Hitachi L-6000 (manufactured by Hitachi, Ltd.)
[0162] Pipeline: 3 pipes in total
[0163] Gelpack GL-R420
[0164] Gelpack GL-R430
[0165] Gelpack GL-R440
[0166] (The above are manufactured by Showa Denko Materials Techno Service Co., Ltd., trade names)
[0167] Eluent: Tetrahydrofuran
[0168] Measurement temperature: 25℃
[0169] Flow rate: 2.05mL / min
[0170] Detector: Hitachi L-3300 RI (manufactured by Hitachi, Ltd.)
[0171] The content of the specific copolymer is preferably 0.01 to 10 parts by mass, more preferably 0.5 to 5 parts by mass, and further preferably 1 to 4 parts by mass relative to 100 parts by mass of the sulfur-containing epoxy resin. If the amount of the specific copolymer is 10 parts by mass or less relative to 100 parts by mass of the sulfur-containing epoxy resin, there is a tendency that sufficient mold release properties can be obtained. If it is 0.5 parts by mass or more, there is a tendency that the improvement effect of adhesion and mold-package contamination becomes sufficient.
[0172] The content of the specific copolymer is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the total of the epoxy resin and the hardener. If the amount of the specific copolymer is 0.01 parts by mass or more relative to 100 parts by mass of the total of the epoxy resin and the hardener, there is a tendency that sufficient mold release properties can be obtained. If it is 10 parts by mass or less, there is a tendency that the improvement effect of adhesion and mold-package contamination becomes sufficient.
[0173] (hardening accelerator)
[0174] The molding resin composition of the present disclosure may contain a curing accelerator as needed. The type of the curing accelerator is not particularly limited, and can be selected based on the type of epoxy resin, the required properties of the molding resin composition, and the like.
[0175] Examples of the curing accelerator include diazabicycloolefins such as 1,5-diazabicyclo[4.3.0]nonene-5 (DBN) and 1,8-diazabicyclo[5.4.0]undecene-7 (DBU), and cyclic amidine compounds such as 2-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 2-ethyl-4-methylimidazole, and 2-heptadecylimidazole; derivatives of the cyclic amidine compounds; and the cyclic amidine compounds or their derivatives. Phenol novolac salts; compounds with intramolecular polarization formed by adding maleic anhydride, 1,4-benzoquinone, 2,5-toluoquinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy-1,4-benzoquinone, phenyl-1,4-benzoquinone and other quinone compounds, compounds with π bonds such as diazonium methane, etc.; cyclic amidinium compounds such as tetraphenylborate of DBU, tetraphenylborate of DBN, tetraphenylborate of 2-ethyl-4-methylimidazole, and tetraphenylborate of N-methylmorpholine; pyridine, triethylamine, triethylenediamine, benzyl Tertiary amine compounds such as dimethylamine, triethanolamine, dimethylaminoethanol, tris(dimethylaminomethyl)phenol; derivatives of the tertiary amine compounds; ammonium salt compounds such as tetra-n-butylammonium acetate, tetra-n-butylammonium phosphate, tetraethylammonium acetate, tetra-n-hexylammonium benzoate, and tetrapropylammonium hydroxide; primary phosphines such as ethylphosphine and phenylphosphine, secondary phosphines such as dimethylphosphine and diphenylphosphine, triphenylphosphine, diphenyl(p-toluene)phosphine, tri(alkylphenyl)phosphine, tri(alkoxyphenyl)phosphine, tri(alkyl-alkoxyphenyl)phosphine, tri(dialkylphenyl)phosphine, tri(trialkylphenyl)phosphine, tri(tetraalkylphenyl)phosphine, tri(dialkoxyphenyl)phosphine, tri(trialkoxyphenyl)phosphine Phosphine, tri(tetraalkoxyphenyl)phosphine, trialkylphosphine, dialkylarylphosphine, alkyldiarylphosphine, trinaphthylphosphine, tri(benzyl)phosphine and other tertiary phosphine and other organic phosphine; phosphine compounds such as complexes of the organic phosphine and organic boron; compounds with intramolecular polarization formed by adding maleic anhydride, 1,4-benzoquinone, 2,5-toluoquinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy-1,4-benzoquinone, phenyl-1,4-benzoquinone, anthraquinone and other quinone compounds, diazonophenylmethane and other compounds with π bonds to the organic phosphine or the phosphine compound;The organic phosphine or the phosphine compound is reacted with 4-bromophenol, 3-bromophenol, 2-bromophenol, 4-chlorophenol, 3-chlorophenol, 2-chlorophenol, 4-iodophenol, 3-iodophenol, 2-iodophenol, 4-bromo-2-methylphenol, 4-bromo-3-methylphenol, 4-bromo-2,6-dimethylphenol, 4-bromo-3,5-dimethylphenol, 4-bromo-2,6-di-tert-butylphenol, 4-chloro-1-naphthol, 1-bromo-2-naphthol, 6- Compounds with intramolecular polarization obtained by reacting halogenated phenol compounds such as bromo-2-naphthol and 4-bromo-4'-hydroxybiphenyl and then undergoing a dehydrohalogenation process; tetraphenyl phosphonium and other tetrasubstituted phosphoniums, tetraphenyl phosphonium tetra-p-toluene borate and other tetraphenyl borate salts of tetrasubstituted phosphoniums; tetrasubstituted phosphonium compounds such as salts of tetrasubstituted phosphonium and phenol compounds; salts of tetraalkyl phosphonium and partial hydrolyzates of aromatic carboxylic anhydrides; phosphate betaine compounds; adducts of phosphonium compounds and silane compounds, etc. ;
[0176] The hardening accelerator may be used alone or in combination of two or more.
[0177] Among these, the curing accelerator is preferably a curing accelerator containing an organic phosphine. Examples of the curing accelerator containing an organic phosphine include phosphine compounds such as the organic phosphine and complexes of the organic phosphine and organic boron, and compounds having intramolecular polarization formed by adding a compound having a π bond to the organic phosphine or the phosphine compound.
[0178] Among these, particularly preferred hardening accelerators include triphenylphosphine, an adduct of triphenylphosphine and a quinone compound; an adduct of tributylphosphine and a quinone compound; and an adduct of tri-p-tolylphosphine and a quinone compound.
[0179] When the molding resin composition contains a hardening accelerator, the amount thereof is preferably 0.1 to 30 parts by mass, more preferably 1 to 15 parts by mass, relative to 100 parts by mass of the total of the epoxy resin and the hardener. If the amount of the hardening accelerator is 0.1 parts by mass or more relative to 100 parts by mass of the total of the epoxy resin and the hardener, there is a tendency to cure well in a short time. If the amount of the hardening accelerator is 30 parts by mass or less relative to 100 parts by mass of the total of the epoxy resin and the hardener, there is a tendency to obtain a good molded product without too fast a hardening speed.
[0180] (Stress Relaxant)
[0181] The molding resin composition disclosed in the present invention may contain a stress relaxant. By including a stress relaxant, the warping deformation of the package and the generation of package cracks can be further reduced. As a stress relaxant, commonly used known stress relaxants (flexible agents) can be cited. Specifically, thermoplastic elastomers such as silicone, styrene, olefin, urethane, polyester, polyether, polyamide, and polybutadiene can be cited; indene-styrene-coumarone copolymers, etc.; organic phosphorus compounds such as triphenylphosphine oxide and phosphate; natural rubber (natural rubber, NR), acrylonitrile butadiene rubber (acrylonitrile butadiene rubber, NBR), acrylic rubber, urethane rubber, silicone powder and other rubber particles; methyl methacrylate-styrene-butadiene copolymer (methacrylate methyl styrenebutadiene, MBS), methyl methacrylate-silicone copolymer, methyl methacrylate-butyl acrylate copolymer and other rubber particles with core-shell structure. The stress relaxant can be used alone or in combination of two or more.
[0182] Examples of the silicone-based stress relaxant include silicone-based stress relaxants having an epoxy group, silicone-based stress relaxants having an amino group, and silicone-based stress relaxants obtained by polyether-modifying these. Silicone compounds such as silicone compounds having an epoxy group and polyether silicone compounds are more preferred.
[0183] From the viewpoint of dielectric loss tangent, the stress relaxation agent preferably includes at least one of an indene-styrene-coumarone copolymer and triphenylphosphine oxide.
[0184] When the molding resin composition contains a stress relaxation agent, the amount thereof is, for example, preferably 1 to 35 parts by mass, more preferably 2 to 34 parts by mass, based on 100 parts by mass of the total of the epoxy resin and the curing agent.
[0185] When the stress relaxer contains at least one of an indene-styrene-coumarone copolymer and triphenylphosphine oxide, the amount thereof is, for example, preferably 1 to 30 parts by mass, more preferably 2 to 20 parts by mass, based on 100 parts by mass of the total of the epoxy resin and the hardener.
[0186] The content of the silicone-based stress relaxant may be, for example, 2 parts by mass or less, or 1 part by mass or less, relative to 100 parts by mass of the total of the epoxy resin and the hardener. The molding resin composition may not contain the silicone-based stress relaxant. The lower limit of the content of the silicone-based stress relaxant is not particularly limited, and may be 0 parts by mass or 0.1 parts by mass.
[0187] From the viewpoint of dielectric loss tangent, the content of the silicone-based stress relaxation agent is preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 7% by mass or less, particularly preferably 5% by mass or less, and extremely preferably 0.5% by mass or less, relative to the entire molding resin composition. The lower limit of the content of the silicone-based stress relaxation agent is not particularly limited, and may be 0% by mass or 0.1% by mass.
[0188] [Various additives]
[0189] The molding resin composition of the present disclosure may contain various additives such as coupling agents, ion exchangers, flame retardants, colorants, etc., in addition to the above components. The molding resin composition of the present disclosure may contain various additives known in the art as needed, in addition to the additives exemplified below.
[0190] (Coupling agent)
[0191] The molding resin composition disclosed herein may include a coupling agent. From the viewpoint of improving the adhesion between the epoxy resin and the hardener and the inorganic filler, the molding resin composition preferably includes a coupling agent. As the coupling agent, there can be cited: silane compounds such as epoxy silane, mercapto silane, amino silane, alkyl silane, ureide silane, vinyl silane, disilazane, titanium compounds, aluminum chelate compounds, aluminum / zirconium compounds and other known coupling agents.
[0192] When the molding resin composition includes a coupling agent, the amount of the coupling agent is preferably 0.05 to 5 parts by mass, more preferably 0.1 to 2.5 parts by mass, relative to 100 parts by mass of the inorganic filler. If the amount of the coupling agent is 0.05 parts by mass or more relative to 100 parts by mass of the inorganic filler, there is a tendency for the adhesion to be further improved. If the amount of the coupling agent is 5 parts by mass or less relative to 100 parts by mass of the inorganic filler, there is a tendency for the moldability of the package to be further improved.
[0193] (Ion Exchanger)
[0194] The molding resin composition disclosed in the present invention may also contain an ion exchanger. From the viewpoint of improving the moisture resistance and high temperature placement characteristics of the electronic component device including the sealed electronic component, the molding resin composition preferably contains an ion exchanger. There is no particular limitation on the ion exchanger, and existing known ion exchangers can be used. Specifically, hydrotalcite compounds and hydroxides containing at least one element selected from the group consisting of magnesium, aluminum, titanium, zirconium and bismuth can be listed. The ion exchanger can be used alone or in combination of two or more. Among them, the hydrotalcite represented by the following general formula (A) is preferred.
[0195] Mg(1-X) Al X (OH)2(CO3) X / 2 ·mH2O……(A)
[0196] (0<X≦0.5, m is a positive number)
[0197] When the molding resin composition contains an ion exchanger, the content thereof is not particularly limited as long as it is a sufficient amount to capture ions such as halogen ions. For example, the content of the ion exchanger is preferably 0.1 to 30 parts by mass, and more preferably 1 to 10 parts by mass, relative to 100 parts by mass of the total of the epoxy resin and the hardener.
[0198] (Flame Retardant)
[0199] The molding resin composition disclosed herein may also contain a flame retardant. The flame retardant is not particularly limited, and any flame retardant known in the art may be used. Specifically, organic or inorganic compounds containing halogen atoms, antimony atoms, nitrogen atoms, or phosphorus atoms, metal hydroxides, and the like may be cited. The flame retardant may be used alone or in combination of two or more.
[0200] When the molding resin composition contains a flame retardant, the amount thereof is not particularly limited as long as it is a sufficient amount to obtain the desired flame retardant effect. For example, the amount of the flame retardant is preferably 1 to 30 parts by mass, and more preferably 2 to 20 parts by mass, relative to 100 parts by mass of the total of the epoxy resin and the hardener.
[0201] (Colorant)
[0202] The molding resin composition disclosed herein may also contain a colorant. As the colorant, known colorants such as carbon black, organic dyes, organic pigments, titanium oxide, red lead, and iron oxide may be cited. The content of the colorant may be appropriately selected according to the purpose, etc. The colorant may be used alone or in combination of two or more.
[0203] (Method for preparing molding resin composition)
[0204] The preparation method of the molding resin composition is not particularly limited. As a general method, the following method can be cited: after the components of the specified blending amount are fully mixed by a mixer, etc., melt-kneading is performed by a grinding roll, an extruder, etc., and then cooled and crushed. More specifically, for example, the following method can be cited: the specified amount of the components is stirred and mixed, and kneaded by a kneader, a roll, an extruder, etc. preheated to 70°C to 140°C, and then cooled and crushed.
[0205] The molding resin composition disclosed in the present invention is preferably solid at normal temperature and pressure (for example, 25° C., atmospheric pressure). The shape of the molding resin composition when it is solid is not particularly limited, and powder, granular, sheet, etc. can be cited. From the perspective of operability, the size and mass of the molding resin composition when it is in sheet form are preferably the size and mass that match the molding conditions of the package.
[0206] (Characteristics of molding resin composition)
[0207] The relative dielectric constant of the cured product of the molding resin composition of the present disclosure at 5 GHz is, for example, 3.3 to 4.0. From the viewpoint of miniaturization of electronic parts such as antennas, the relative dielectric constant of the cured product at 5 GHz is preferably 3.3 to 3.8, more preferably 3.3 to 3.6, and even more preferably 3.3 to 3.5.
[0208] The relative dielectric constant is measured at a temperature of 25±3° C. using a dielectric constant measuring device (eg, a cavity resonator).
[0209] In order to make the relative dielectric constant of the cured product at 5 GHz be 3.3 to 3.5, it is preferable to use an active ester compound as a curing agent.
[0210] The dielectric loss tangent at 5 GHz of the cured product of the molding resin composition disclosed herein may be, for example, 0.08 or less. From the viewpoint of reducing transmission loss, the dielectric loss tangent at 5 GHz of the cured product is preferably 0.04 or less, more preferably 0.02 or less, and further preferably 0.01 or less. The lower limit of the dielectric loss tangent at 5 GHz of the cured product is not particularly limited, and may be, for example, 0.001.
[0211] The dielectric loss tangent is measured at a temperature of 25±3° C. using a dielectric constant measuring device (eg, a cavity resonator).
[0212] In order to make the dielectric loss tangent of the cured product at 5 GHz be 0.01 or less, it is preferable to use an active ester compound as a curing agent.
[0213] (Application of molding resin composition)
[0214] The molding resin composition disclosed herein can be applied to, for example, electronic component devices described later, and is particularly suitable for the manufacture of high-frequency devices. The molding resin composition disclosed herein can also be used for sealing electronic components in high-frequency devices. When the molding resin composition disclosed herein is used for sealing electronic components in high-frequency devices, it is preferred to use an active ester compound as a curing agent.
[0215] In particular, in recent years, with the popularization of the fifth-generation mobile communication system (5G), the high-functionality and miniaturization of semiconductor packages (PKG) used for electronic parts devices have continued to develop. In addition, with the miniaturization and high-functionality of PKG, the development of antenna system packages (Antenna in Package, AiP) as PKGs with antenna functions is also underway. In AiP, in order to cope with the increase in the number of channels accompanying the diversification of information, the radio waves used in communication are high-frequency, and low dielectric loss tangent and low dielectric constant are required in the sealing material.
[0216] As described above, the molding resin composition disclosed herein can obtain a cured product with a low dielectric loss tangent and dielectric constant by using an active ester compound as a curing agent. Therefore, in high-frequency devices, it is particularly suitable for antenna system package (AiP) applications in which an antenna arranged on a supporting member is sealed with a molding resin composition.
[0217] In an electronic component device including an antenna such as an antenna system package, when an amplifier for power supply is arranged on the side opposite to the antenna, heat is generated due to power supply. From the viewpoint of improving heat dissipation, the molding resin composition used in the manufacture of the electronic component device preferably contains alumina particles as an inorganic filler.
[0218] <Electronic components and devices>
[0219] The electronic component device disclosed herein includes a supporting member, an electronic component disposed on the supporting member, and a cured product of the molding resin composition that seals the electronic component.
[0220] Examples of electronic component devices include electronic component devices (e.g., high-frequency devices) in which electronic components (active components such as semiconductor chips, transistors, diodes, thyristors, etc., passive components such as capacitors, resistors, coils, antennas, etc.) are mounted on support members such as lead frames, conveyor tapes with completed wiring, wiring boards, glass, silicon wafers, organic substrates, etc., and the electronic component area is sealed with a molding resin composition.
[0221] The type of the supporting member is not particularly limited, and a supporting member generally used in the manufacture of electronic component devices can be used.
[0222] The electronic component may include an antenna, or may include an antenna and an element other than an antenna. The antenna is not limited as long as it functions as an antenna, and may be an antenna element or wiring.
[0223] In addition, in the electronic component device of the present disclosure, other electronic components may be arranged on the surface of the support member opposite to the surface on which the electronic components are arranged, as needed. Other electronic components may be sealed by the molding resin composition, may be sealed by other resin compositions, or may not be sealed.
[0224] (Method for manufacturing electronic component device)
[0225] The method for manufacturing an electronic component device disclosed herein includes: a step of arranging an electronic component on a supporting member; and a step of sealing the electronic component with the molding resin composition.
[0226] The method for carrying out each of the above steps is not particularly limited and can be carried out by a general method.
[0227] In addition, the types of the support member and the electronic component used in the manufacture of the electronic component device are not particularly limited, and the support member and the electronic component generally used in the manufacture of the electronic component device can be used.
[0228] Examples of methods for sealing electronic components using the molding resin composition include low-pressure transfer molding, injection molding, compression molding, etc. Among these, the low-pressure transfer molding method is generally used.
[0229] [Example]
[0230] Hereinafter, the embodiment will be described in detail by way of examples, but the scope of the embodiment is not limited to these examples.
[0231] <Preparation of molding resin composition>
[0232] The molding resin compositions of Examples and Comparative Examples were prepared by mixing the following components at the blending ratios (parts by mass) shown in Tables 1 and 2. The molding resin compositions are solid at normal temperature and pressure.
[0233] Tables 1 and 2 also show the content of the inorganic filler relative to the entire molding resin composition ("filler amount (volume %)" in the table).
[0234] Epoxy resin 1: triphenylmethane type epoxy resin (epoxy equivalent: 167g / eq)
[0235] · Epoxy resin 2: represented by general formula (B), and R 10 The positions of the oxygen atoms in the molecule are 4-position and 4'-position, 3-position and 3'-position are tert-butyl, 6-position and 6'-position are methyl, and the other R 10 Compounds containing hydrogen atoms (epoxide equivalent 245 g / eq)
[0236] Epoxy resin 3: Bisphenol F type epoxy resin (epoxy equivalent: 193g / eq)
[0237] Epoxy resin 4: biphenyl aralkyl type epoxy resin (epoxy equivalent 277g / eq)
[0238] Epoxy resin 5: biphenyl type epoxy resin (epoxy equivalent: 196g / eq)
[0239] Epoxy resin 6: o-cresol novolac type epoxy resin (epoxy equivalent 200g / eq)
[0240] · Hardener 1: triphenylmethane type phenol resin (hydroxyl equivalent: 106g / eq)
[0241] Hardener 2: Melamine-modified phenol resin (hydroxyl equivalent: 120 g / eq)
[0242] Hardener 3: Biphenyl aralkyl type phenol resin (hydroxyl equivalent: 200 g / eq)
[0243] Hardener 4: Active ester compound, DIC Corporation, product name "EXB-8"
[0244] · Hardening accelerator: adduct of tributylphosphine and 1,4-benzoquinone
[0245] · Coupling agent 1: diphenyldimethoxysilane
[0246] · Coupling agent 2: N-phenyl-3-aminopropyltrimethoxysilane
[0247] Coupling agent 3: methyltrimethoxysilane
[0248] · Coupling agent 4: 3-glycidyloxypropyltrimethoxysilane
[0249] Release agent 1: Hoechst wax (Clariant Chemicals Co., Ltd., trade name "HW-E")
[0250] Release agent 2: linear oxidized polyethylene, weight average molecular weight 8800, acid value 30mgKOH / g
[0251] Release agent 3: branched oxidized polyethylene, weight average molecular weight 3100, acid value 25 mgKOH / g
[0252] Release agent 4: linear oxidized polyethylene, weight average molecular weight 11000, acid value 30mgKOH / g
[0253] Release agent 5: oxidized polyethylene, weight average molecular weight 7500, acid value 28 mgKOH / g
[0254] · A specific copolymer: comprising a structural unit represented by the general formula (C) and a structural unit represented by the general formula (D), wherein the molar ratio X / Y of the structural unit represented by the general formula (C) and the structural unit represented by the general formula (D) is 1 / 1, and R in the general formula (C) 11 is n-octadecyl, n-eicosyl or n-heneicosyl, and R in the general formula (D) 12 and R 13 A copolymer containing 1-eicosene, 1-eicosene and 1-eicosene as raw materials (weight average molecular weight: 20400)
[0255] Colorant: Carbon black
[0256] Additive 1: Epoxy equivalent 2900g / eq, viscosity 2850mm 2 / s(25℃) silicone oil
[0257] Additive 2: triphenylphosphine oxide
[0258] Additive 3: polysiloxane with epoxy equivalent weight of 1660 g / eq and softening point of 80°C
[0259] Inorganic filler 1: Silica particles (volume average particle size: 0.6 μm)
[0260] Inorganic filler 2: magnesium hydroxide particles (volume average particle size: 1.5 μm)
[0261] Inorganic filler 3: Silica particles (volume average particle size: 27 μm)
[0262] Inorganic filler 4: Silica particles (volume average particle size: 16 μm)
[0263] Inorganic filler 5: Silica particles (volume average particle size: 11 μm)
[0264] Inorganic filler 6: Silica particles (volume average particle size: 2.3 μm)
[0265] Inorganic filler 7: Silica particles (volume average particle size: 30 μm)
[0266] Inorganic filler 8: Silica particles (specific surface area 190m 2 / g~230m 2 / g of nano-silicon dioxide particles)
[0267] Inorganic filler 9: Silica particles (volume average particle size: 17 μm)
[0268] Inorganic filler 10: Silica particles (volume average particle size: 1.5 μm)
[0269] Inorganic filler 11: Silica particles (volume average particle size: 16 μm)
[0270] Inorganic filler 12: Silica particles (volume average particle size: 31 μm)
[0271] Inorganic filler 13: Silica particles (volume average particle size: 4.0 μm)
[0272] Inorganic filler 14: Silica particles (volume average particle size: 0.5 μm)
[0273] In addition, the volume average particle size of each of the inorganic fillers is a value obtained by the following measurement.
[0274] Specifically, first, an inorganic filler is added to a dispersion medium (water) in a range of 0.01 mass % to 0.1 mass %, and the mixture is dispersed for 5 minutes using a bath type ultrasonic cleaning machine.
[0275] 5 ml of the obtained dispersion was poured into a tank, and the particle size distribution was measured at 25°C using a laser diffraction scattering particle size distribution measuring apparatus (Horiba, Ltd., LA920).
[0276] The particle diameter of the cumulative value of 50% (volume basis) in the obtained particle size distribution was defined as the volume average particle diameter.
[0277] The specific surface area of the inorganic filler 8 is a value measured based on nitrogen adsorption capacity in accordance with JIS Z 8830:2013.
[0278] (Evaluation of spiral flow (SF))
[0279] The molding resin composition was molded by a transfer molding machine at a mold temperature of 180°C, a molding pressure of 6.9 MPa, and a curing time of 120 seconds using a spiral flow measurement mold in accordance with EMMI-1-66, and the flow distance (inch) was determined. The results are shown in Tables 3 and 4.
[0280] (Determination of gelation time (GT))
[0281] 0.5 g of a molding resin composition as a sample was placed on a hot plate heated to 175° C., and the sample was uniformly expanded into a circle with a diameter of 2.0 cm to 2.5 cm at a rotation speed of 20 to 25 rpm using a jig.
[0282] The time from when the sample was placed on the hot plate until the stickiness of the sample disappeared and the sample became a gel state and was peeled off the hot plate was measured, and this was referred to as the gel time (sec).
[0283] (Evaluation of hot hardness)
[0284] The hot hardness of the thermosetting resin composition was evaluated as follows.
[0285] The thermosetting resin composition was molded into a test piece (a circular plate with a diameter of 50 mm and a thickness of 3 mm) for measuring the hardness when hot by a transfer molding machine at a mold temperature of 175°C to 180°C, a molding pressure of 6.9 MPa, and a curing time of 90 seconds. Immediately after molding, the hot hardness (Shore D) of the test piece was measured using a Shore D type hardness tester. The results are shown in Tables 3 and 4.
[0286] (Bending strength evaluation)
[0287] The molding resin compositions of Example 6 and Comparative Example 4 were molded using a transfer molding machine at a molding temperature of 175°C, a molding pressure of 6.9 MPa, and a curing time of 120 seconds to obtain a plate-shaped molded product (127 mm in length, 12.7 mm in width, and 4 mm in thickness). This was used as Test Piece 1. Subsequently, Test Piece 1 was post-cured at 175°C for 5 hours to obtain a plate-shaped cured product (127 mm in length, 12.7 mm in width, and 4 mm in thickness). This was used as Test Piece 2.
[0288] The bending strength (MPa) of the test pieces 1 and 2 was measured using Autograph (manufactured by Shimadzu Corporation, bending tester AG-500).
[0289] (Determination of relative dielectric constant and dielectric loss tangent)
[0290] The molding resin composition of Example 6 and Comparative Example 4 was loaded into a transfer molding machine and molded under the conditions of a mold temperature of 180°C, a molding pressure of 6.9 MPa, and a curing time of 120 seconds. Post-curing was performed at 175°C for 6 hours to produce a rectangular test piece of 90 mm × 0.6 mm × 0.8 mm.
[0291] The relative dielectric constant (Dk) and dielectric loss factor (Df) of the test piece were measured at a frequency of 5 GHz using a cavity resonator (Kanto Electronics Application Development Co., Ltd.) and a network analyzer (Keysight Technologies, product name "PNA E8364B") at a temperature of 25±3°C. The results are shown in Table 4.
[0292] (Evaluation of mold release properties)
[0293] The molding resin composition was compression molded into a disk shape on a ferromagnetic board (35 mm×50 mm×0.5 mm) with a hard chrome plated surface. The disk had an area of 3.14 cm 2 The molding resin composition was molded at a molding temperature of 175° C., a molding time of 90 seconds, and a molding pressure of 10 MPa.
[0294] Then, the cured product was fixed using a surface adsorption machine, and the ferromagnetic plate was pulled out horizontally relative to the interface between the cured product and the ferromagnetic plate to peel the cured product from the ferromagnetic plate. The shear demolding force (shear demolding strength) required to peel the cured product from the ferromagnetic plate was read using a push pull gauge (manufactured by IMADA Co., Ltd., with a maximum scale of 500 (N)).
[0295] At the location where the hardened material was peeled off from the ferromagnetic plate after the shear demolding force measurement was completed, the molding resin composition was compression molded into a disk shape again, and the shear demolding force was then measured. The above operation was repeated 10 times in total. The measurement results are shown in Tables 3 and 4. In addition, the changes in the shear demolding strength during each measurement are shown in Tables 3 and 4. Figure 1 and Figure 2 In addition, Figure 2 In the figure, the solid line represents the result of Example 6, and the dotted line represents the result of Comparative Example 4.
[0296] [Table 1]
[0297] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Epoxy resin 1 45 Epoxy Resin 2 30 30 25 30 30 Epoxy Resin 3 70 70 70 70 70 75 75 Epoxy Resin 4 30 Epoxy Resin 5 30 25 25 Hardener 1 42.2 42.2 22.3 34.6 31.6 36.6 50.7 50.7 Hardener 2 5.98 6 6 Hardener 3 20.2 20.2 42.7 24.8 30.4 37.7 10.8 10.8 Hardening accelerator 4 4 1.8 3.3 4 3.6 3.4 3.4 Coupling agent 1 4.5 4.5 4.5 4.5 3 Coupling agent 2 6.8 6.8 4.5 6.8 6.8 6.8 6.8 6.8 Coupling agent 3 4.5 4.5 Release agent 1 1 1 1 1 1 1 1 1 Release agent 2 1.5 1.5 1.3 1.5 1.5 3 Release agent 3 1.5 1.5 1.3 1.5 1.5 1.5 1.5 Release agent 4 1 1 Specific copolymers 0.75 0.75 0.6 0.75 0.75 1.5 0.5 0.5 Colorants 3.5 3.5 2.6 3.5 3.5 3.5 5.2 5.2 Additive 1 3 3 1.5 1 1 Additive 2 10 10 12.5 15 10 5 5 Additive 3 10 10 30 40 40 8 8 Filler content (volume %) 82 82 79 81 81 82 82 82 Inorganic filler 1 178 178 145 196 201 182 105 105 Inorganic filler 2 93 Inorganic filler 3 1315 Inorganic filler 4 730 730 1091 1398 Inorganic filler 5 365 365 Inorganic filler 6 183 183 Inorganic filler 7 365 365 Inorganic filler 8 5 5 Inorganic filler 9 1767 1809 546 Inorganic filler 10 70 70 Inorganic filler 11 1573 Inorganic filler 12 175 total 2034.95 2034.95 1767.08 2203.75 2256.55 2027.2 1947.4 1947.4
[0298] [Table 2]
[0299] Comparative Example 4 Example 6 Epoxy Resin 6 75 75 Epoxy Resin 2 25 Epoxy Resin 5 25 Hardener 4 108 102 Hardening accelerator 3.5 3.5 Coupling agent 2 5 5 Coupling agent 4 1 1 Colorants 2.6 2.6 Release agent 5 2.5 2.5 Specific copolymers 0.3 0.6 Filler content (volume %) 72 72 Inorganic filler 13 878 856 Inorganic filler 14 220 214 total 1320.6 1286.6
[0300] [Table 3]
[0301] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 GT(seconds) 47 49 40 66 64 58 40 42 SF[inch] 66.2 67.1 29.4 61.7 52.2 71.1 55.2 54.3 Hardness when hot 83 83 86 79 83 86 88 89 Shear demoulding strength (N) 1st time 210 140 200 135 160 190 190 200 2nd time 160 140 150 90 90 190 190 200 3rd 160 140 140 40 70 190 190 210 4th 150 65 90 20 40 165 190 150 5th 140 45 100 50 10 145 190 210 6th 0 45 60 25 15 120 170 200 7th 0 40 60 25 5 100 170 190 8th 0 45 40 40 0 50 170 200 9th 0 50 30 5 25 0 170 200 10th 0 35 40 40 0 0 120 190
[0302] [Table 4]
[0303] Comparative Example 4 Example 6 GT(seconds) 48 51 SF[inch] 55.9 49.2 Hardness when hot 80 81 Bending strength (test piece 1, MPa) 105 116 Bending strength (test piece 2, MPa) 130 135 Dk 3.46 3.48 Df 0.0025 0.0024 Shear demoulding strength (N) 1st time 230 280 2nd time 230 140 3rd 200 100 4th 200 60 5th 80 60 6th 80 60 7th 80 50 8th 60 50 9th 50 40 10th 40 40
[0304] As is clear from the evaluation results in Table 3, Examples 1 to 5 using a phenol curing agent have a more rapid decrease in shear release strength than Comparative Examples 1 to 3, and are found to be excellent in releasability.
[0305] As is clear from the evaluation results in Table 4, it is understood that Example 6 using an active ester compound as a curing agent has a more rapid decrease in shear release strength than Comparative Example 4, and is excellent in releasability.
[0306] The entire contents of the disclosure of Japanese Patent Application No. 2022-186879 filed on November 22, 2022 are incorporated into this specification by reference.
[0307] All documents, patent applications, and technical specifications described in this specification are cited and incorporated into this specification to the same extent as if each document, patent application, or technical specification was specifically and individually described as being incorporated by reference.
Claims
1. A molding resin composition comprising: a sulfur-containing epoxy resin; a hardener; a release agent; an inorganic filler; and a copolymer of an α-olefin having 5 to 30 carbon atoms and at least one of maleic anhydride and a maleic anhydride derivative.
2. The molding resin composition according to claim 1, wherein The sulfur-containing epoxy resin comprises a compound represented by the following general formula (B); [Chemistry 1] (In general formula (B), R 10 represents a hydrogen atom or a monovalent organic group having 1 to 18 carbon atoms, which may be all the same or different; n is an average value and represents a number from 0 to 10).
3. The molding resin composition according to claim 1, wherein The mold release agent comprises oxidized polyethylene.
4. The molding resin composition according to claim 3, wherein The oxidized polyethylene includes a linear oxidized polyethylene.
5. The molding resin composition according to claim 3, wherein The oxidized polyethylene includes branched oxidized polyethylene.
6. The molding resin composition according to claim 3, wherein The weight average molecular weight of the oxidized polyethylene is greater than 2800.
7. The molding resin composition according to claim 3, wherein The acid value of the oxidized polyethylene is 2 mgKOH / g to 50 mgKOH / g.
8. The molding resin composition according to claim 1, wherein The copolymer comprises a structural unit represented by the following general formula (C) and a structural unit represented by the following general formula (D); [Chemistry 2] (In general formula (C) and general formula (D), R 11 represents a monovalent aliphatic hydrocarbon group having 3 to 28 carbon atoms, R 12 and R 13 each independently represents a hydrogen atom, an alkyl group or an aryl group).
9. An electronic component device comprising: Supporting members; Electronic components are arranged on the supporting member; And a cured product of the molding resin composition according to any one of claims 1 to 8, which seals the electronic component.
Citation Information
Patent Citations
Epoxy resin composition for semiconductor sealing
JP1998036486A
Epoxy resin molding material for sealing, and electronic part device
JP2001247748A
Epoxy resin molding material for sealing and electronic parts device
JP2003064239A
Epoxy resin molding material for sealing and electronic part apparatus
JP2005255978A
Sealing epoxy resin molding material and electronic component device
JP2006182913A